PENGEMBANGAN MEDIA PEMBELAJARAN KARTU SUKU KATA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AWAL SISWA KELAS I SD NEGERI 060820 MEDAN - Muhammad Rizki Ridwan Rambe; Juliandi Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop syllable card media to improve early reading skills in elementary schools. The research method used is RnD with the ADDIE development model: analyze, design, development, implementation, and evaluation. This research was conducted at State Elementary School 060820 Medan City with 22 students as subjects. Data collection techniques used were observation, interviews, documentation, questionnaires, and tests. The results of the study indicate that the syllable cards met the validity criteria, with a score of 84% from the material expert validator, 82% from the media expert validator, and 92% from the language expert validator, with an average validation score of 86%, categorized as very valid. The developed syllable card media product also met the criteria of being very practical, based on teacher responses of 94%. The syllable cards were also declared effective in improving students' reading skills, with a pretest score of 68% and a posttest score increasing to 92%, indicating a significant increase of 24%. Therefore, it can be concluded that the developed syllable card learning media has met the criteria of validity, practicality, and effectiveness, making it suitable for use as a learning medium to improve students' early reading skills.